The strengths and complexities of European registries concerning paediatric kidney transplantation health care - Oomen, Loes; De Wall, Liesbeth L.; Krupka, Kai; Tönshoff, Burkhard; Wlodkowski, Tanja; Van Der Zanden, Loes FM; Bonthuis, Marjolein; Duus Weinreich, Ilse D.; Koster-Kamphuis, Linda; Feitz, Wout FJ; Bootsma-Robroeks, Charlotte MHHT (Frontiers in Pediatrics, 2023)
Patient data are increasingly available in (multi)national registries, especially for rare diseases. This study aims to provide an overview of current European registries of paediatric kidney transplantation (PKT) care, their coverage, and their focus. Based on these data, we assess whether the current status is optimal for achieving our common goal: the optimalisation of health care. A list of all PKT centres within the European Union (EU) as well as active PKT registries was compiled using existing literature and the European Platform on Rare Disease Registration. Registry staff members were contacted to obtain information about the parameters collected and the registry design. These data were compared between registries. In total, 109 PKT centres performing PKT surgery were identified in the 27 EU Member States. Currently, five European PKT registries are actively collecting data. In 39% of these centres, no data were registered within any of these five existing international registries. A large variety was observed in the number of patients, centres, and countries involved in the registries. Furthermore, variability existed regarding the inclusion criteria, definitions used, and parameters collected. Collection of perioperative urologic data are currently underrepresented in the registries. Currently, multiple registries are collecting valuable information in the field of PKT, covering the majority of PKT centres in Europe. Due to a large variety in the parameters collected as well as different focuses, data collection is currently fragmented and suboptimal; therefore, the current existing data are incomplete. In addition, a considerable proportion of the transplantation centres do not enter data in any international registry. Combining available information and harmonising future data collection could empower the aim of these registriesa, namely increasing insights into the strengths and potential of current care and therefore improve healthcare